Peningkatan Kualitas Tidur Lansia yang Mengalami Kecemasan pada Masa Pandemi COVID-19 dengan Terapi Murottal Al-Qur’an - Dini Tryastuti (Journal of Telenursing (JOTING), 2022)
This study aims to identify the effectiveness of murottal Al-Qur'an therapy in overcoming decreased sleep quality in the elderly who experience anxiety during the COVID-19 pandemic. The method used is a quasi-experimental with a control group of 44 respondents who were selected by purposive sampling. The intervention and control groups each amounted to 22 respondents. Therapy was given to the intervention group for ± 10 minutes before going to bed for 1 week by playing Murrottal Al-Qur'an through an MP4 Player that has been filled with Murottal Al-Qur'an recording data. The results of this study indicate that there is an effect of murottal Al-Qur'an on sleep quality (p-value 0.001). In conclusion, murottal Al-Qur'an therapy is effective in improving the sleep quality of the elderly who experience anxiety during the COVID-19 pandemic. Keywords: Sleep Quality, Elderly, COVID-19 Pandemic, Murottal Al-Qur'an Therapy